How to critique authoritarian populism : methodologies of the Frankfurt School - Morelock, Jeremiah (Studies in critical social sciences, 2021)
"How to Critique Authoritarian Populism: Methodologies of the Frankfurt School offers a comprehensive introduction to the techniques used by the early Frankfurt School to study and combat authoritarianism and authoritarian populism. In recent years there has been a resurgence of interest in the writings of the early Frankfurt School, at the same time as authoritarian populist movements are resurging in Europe and the Americas. This volume shows why and how Frankfurt School methodologies can and should be used to address the rise of authoritarianism today. Critical theory scholars are assembled from a variety of disciplines to discuss Frankfurt School approaches to dialectical philosophy, psychoanalytic theory, human subjects research, discourse analysis and media studies. Contributors include: Robert J. Antonio, Stefanie Baumann, Christopher Craig Brittain, Dustin J. Byrd, Mariana Caldas Pinto Ferreira, Panayota Gounari, Peter-Erwin Jansen, Imaculada Kangussu, Douglas Kellner, Dan Krier, Lauren Langman, Claudia Leeb, Gregory Joseph Menillo, Jeremiah Morelock, Felipe Ziotti Narita, Michael R. Ott, Charles Reitz, Avery Schatz, Rudolf J. Siebert, William M. Sipling, David Norman Smith, Daniel Sullivan, and AK Thompson"--